FEMININITAS DAN KEKUASAAN - Widjajanti Santoso (LIPI Press, 2008)
This article shows the change and continuity of femininity construction in Indonesian public using the media. It started with the femininity construction during the colonial era, which showed how femininity was used by the colonial government and by the Indonesian movement at that time. It was a public space construction, which negotiated places to support some types of femininity construction. By describing this construction process, the article wish to show that power plays an important role. Being feminine women is not of women wish but more on how the society at large preserve some types of femininity discourse. The article also shows that such construction process at the end is also a big demand from capitalistic interest. The capital and the global are two other sources of power that at present depict what kind of women to be constructed.